Singlet oxygen quantum yields from halogenated chlorins: potential new photodynamic therapy agents - Pineiro, Marta (2001)
Flash photolysis and photoacoustic calorimetry were used to measure the energy-transfer rates and singlet oxygen quantum yields originated by the triplet states of halogenated tetrakisphenylporphyrins and related chlorins in aerated toluene. The chlorins ([lambda]max[approximate]660 nm, [var epsilon][approximate]3×104 M-1 cm-1) have long-lived triplet states (>12 [mu]s) in the absence of molecular oxygen, and in its presence the singlet oxygen production quantum yields of the 2-chloro and 2,6-dichlorophenyl derivatives are 0.89±0.05 and 0.98±0.02, respectively. The high absorptivity in the red, the photostability and the efficiency of these chlorins in producing singlet oxygen suggests a ground for the development of better sensitisers for photodynamic therapy.